MAKANAN, OBAT-OBATAN SERTA KOSMETIK ILEGAL DALAM EFEKTIVITAS HUKUM ISLAM DAN UUJPH DI ACEH - jaidatul fikri Binti Muhammad (State of Islamic Institute Langsa, 2019)
Medicine, cosmetics and food safety issues are the issues have not been discussed until today. The presence of Law No. 33 of 2014 concerning Halal Product Guarantee (UUJPH) is expected to be able to enlighten the hopes of Muslims about the status of food products, medicines and cosmetics which are partly circulated freely without the halal label and are safe to consume and quite unsettling. This is the purpose of this writing raised. This paper is part of the results of the 2017 BOPTN research, but similar findings are still found in 2019. The research methodology used is qualitative methodology with observation and interview techniques. Interviews were also conducted with the head of the Aceh MPU, the Aceh MPU LPPOM agency and several other religious and community leaders. Several findings and final conclusions show that UUJPH has not been able to regulate binding rules because this law is still voluntary, against the use of drugs (including herbal medicine), cosmetics, and food and beverage drinks that do not have a halal label and are indicated dangerous categorized as doubtful. according to Islamic law.